Peran Strategis Guru dalam Membentuk Karakter Anak Usia Dini: Studi Kasus di RA GUPPI Gondosaric - Fitri, Ice Lisa; Prahastiwi, Eka Danik (Lembaga Yasin AlSys, 2025)
This study aims to examine the role of teachers in shaping the character of early childhood at RA GUPPI Gondosari. Teachers have an important role iin shaping the character of early childhood through directed and loving education. At this stage, critical period of development, where basic values such as honesty, responsibility, empathy and discipline begin to form. Teachers not only act as educators, but also as role models who provide real examples of positive behavior. Through daily interactions, teachers help children understand social norms, manage emotions, and build healthy relationships with peers and the surrounding environment. Character education provided by teachers is often carried out through playing, telling stories, or fun group discussions. These activities are designed to instill moral values in a way that is relevant and easy for children to understand. Teachers also create a supportive learning environment, where children feel safe to explore, learn and interact. With a warm and caring approach, teachers help children develop self-confidence and the ability to recognize and overcome challenges.